Quantitative reproducibility analysis for identifying reproducible targets from high-throughput experiments - Zhang, Wenfei; Liu, Ying; Zhang, Mindy; Zhu, Cheng; Lu, Yuefeng (BMC systems biology, 2017)
Background High-throughput assays are widely used in biological research to select potential targets. One single high-throughput experiment can efficiently study a large number of candidates simultaneously, but is subject to substantial variability. Therefore it is scientifically important to performance quantitative reproducibility analysis to identify reproducible targets with consistent and significant signals across replicate experiments. A few methods exist, but all have limitations. Methods In this paper, we propose a new method for identifying reproducible targets. Considering a Bayesian hierarchical model, we show that the test statistics from replicate experiments follow a mixture of multivariate Gaussian distributions, with the one component with zero-mean representing the irreproducible targets. Results A target is thus classified as reproducible or irreproducible based on its posterior probability belonging to the reproducible components. We study the performance of our proposed method using simulations and a real data example. Conclusion The proposed method is shown to have favorable performance in identifying reproducible targets compared to other methods.